(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
To address the challenges faced by wheelchair users living alone when it comes to wearing trousers, this paper aims to enhance the design of existing trousers by focusing on adaptive structure design and wearing convenience. It also proposes a design concept for wheelchair trouser integration. For adaptive structure design, the structure of the trousers is adapted to the corresponding parts of the wheelchair to obtain an enhanced trouser pattern. Through clo3d virtual fitting verification, the pressure distribution effect of trousers in a sitting posture improved. The connection between the back of the pants and the wheelchair seat is designed to achieve optimal stabilisation. The U-shaped opening design of the wheelchair seat allows for proper storage of the front of the pants, enabling quick circulation and enhancing the independence of wheelchair users. A wear trial experiment was conducted to evaluate the convenience of the prototype trousers. This involved calculating the wearing time and independent coefficient, which provided evidence that the proposed integrated wheelchair trouser design significantly improves wearing convenience.